Innovations in the Treatment of Antibiotic-Resistant Bacterial Infections: From Drugs to Alternative Approaches - Fadhil, Noor Muneam (Majallat Jāmiʻat Bābil, 2025)
Infections resulting from antibiotic-resistant bacteria (ARB) represent a major global health concern of our era. Alongside the development of novel antibiotics, the identification of antibiotic-resistant microorganisms and the exploration of alternatives to current medications present viable strategies to address antibiotic resistance. This analysis consolidates the most promising solutions for combating ARB that are currently in development. These strategies encompass: (a) the discovery of novel antibiotics through the modification of existing compounds; (b) the enhancement of the efficacy of current antibiotics via metabolic stimulation or the implementation of advanced delivery systems; and (c) the emergence of novel alternatives to traditional antibiotics includes bacteriophages and endolysins, anti-biofilm compounds, probiotics, nanomaterials, vaccines, and antibody-based therapies. Preclinical and clinical investigations indicate that these treatments possess significant potential against antibiotic-resistant microorganisms. Certain ARB items are anticipated to be commercially accessible in the imminent future.